Anode material of proton ceramic fuel cell, preparation method and application of anode material in direct ammonia fuel cell

By directly adding Ni elements to the anode material, Ni-BaZr0.1Ce0.7Y0.1Yb0.1O3-δ composite anode material is formed, which solves the problem of instability of Ni-based anode in the ammonia environment, and improves the catalytic activity of ammonia gas and machinery. The strength significantly improves the electrochemical performance and stability of direct ammonia proton ceramic fuel cells.

CN119400875APending Publication Date: 2025-02-07NANJING TECH UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411574778.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The Ni-based anode of direct ammonia proton ceramic fuel cell is easily reacted with ammonia, forming unstable nickel nitride, resulting in active site consumption, increased activation overpotential, mechanical stress changes and interface characteristics, which in turn affects the stability and mechanical properties of the battery. strength.

Method used

The Ni element is directly added to the anode material by a one-step method to form Ni-BaZr0.1Ce0.7Y0.1Yb0.1O3-δ composite anode material, which improves the three-phase interface and mechanical strength, and is prepared by sol-gel method to enhance the ammonia gas Catalytic activity.

Benefits of technology

The catalytic activity and stability of the anode material to ammonia is improved, the mechanical strength is enhanced, the impedance of the material is reduced, and the electrochemical performance and stability of the battery is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005121503700000011
    Figure HDA0005121503700000011
  • Figure HDA0005121503700000021
    Figure HDA0005121503700000021
  • Figure HDA0005121503700000022
    Figure HDA0005121503700000022
Patent Text Reader

Abstract

The invention relates to a preparation method of a proton ceramic fuel cell anode material and application of the proton ceramic fuel cell anode material in a direct ammonia fuel cell, and belongs to the technical field of fuel cell electrode materials. The composition molecular formula of the anode material is Ni-BaZr0. 1Ce0. 7Y0. 1Yb0. 1O3-delta. The anode material Ni-BaZr0. 1Ce0. 7Y0. 1Yb0. 1O3-delta is prepared by using a one-step method, so that the mechanical strength and the conductivity of the anode of the fuel cell are improved, and the impedance of the material is reduced. According to the Ni-BaZr0. 1Ce0. 7Y0. 1Yb0. 1O3-delta anode material prepared by a one-step method, the electrochemical performance of a fuel cell can be effectively improved, the practicability of the proton ceramic direct ammonia fuel cell is improved, and the commercialization progress of the proton ceramic direct ammonia fuel cell is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a proton ceramic fuel cell anode material, a preparation method and use in a direct ammonia fuel cell, and specifically relates to a composite anode material Ni-BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ The preparation method and application belong to the technical field of fuel cell electrode materials. Background Art

[0002] In order to balance the mismatch between electricity supply and demand and alleviate the deteriorating ecological and climatic conditions caused by over-reliance on fossil fuels for power generation, it is urgent to develop renewable energy to replace traditional energy forms. Solid oxide fuel cells (SOFCs) have advantages in efficient conversion of chemical energy to electrical energy and wide fuel adaptability due to their internal solid-state ion transport, high operating temperature, and fast electrochemical reaction. Compared with SOFCs, proton ceramic fuel cells (PCFCs) show the potential for efficient power generation at lower operating temperatures, which can reduce costs, prevent rapid deactivation of catalysts, and extend the service life of the battery. However, hydrogen, as the most widely used fuel for PCFCs, faces global challenges such as low production efficiency, poor infrastructure development, and high safety risks. Therefore, finding suitable alternatives to hydrogen is more conducive to the commercialization of PCFCs.

[0003] As a carbon-free hydrogen carrier, ammonia has the advantages of high production, easy storage and transportation. Considering that the combustion temperature of ammonia in air is higher than that of hydrogen and alkanes, and that NO is produced during its combustion, xReplacing hydrogen with ammonia as a fuel for PCFCs is a feasible solution to address the shortcomings of hydrogen in large-scale applications. Therefore, the development of direct ammonia proton ceramic fuel cells has greater commercial prospects and appeal. Although direct ammonia proton ceramic fuel cells have high potential, some pressing issues must be addressed before commercialization. Unlike the cathode where the oxygen reduction reaction occurs and the ceramic electrolyte for ion conduction, the anode of direct ammonia proton ceramic fuel cells is crucial to promote the ammonia decomposition reaction. The structure and composition of the anode directly affect the efficiency and stability of the cell. Currently, the widely used nickel-based anodes are less active in the ammonia decomposition reaction, and more efficient catalysts are needed to reduce the starting potential of the reaction and increase the current density. In addition to the need for effective ammonia decomposition catalysts, the tolerance and structural evolution of Ni-based anodes in ammonia environments are also key factors that hinder the improvement of battery performance and stability. Conventional Ni-based anodes easily react with ammonia to form compounds such as nickel nitride (Ni3N), which consumes active sites on the nickel surface and increases the activation overpotential. More importantly, these unstable nitrides may partially decompose or transform at high temperatures, resulting in repeated nitridation and reduction cycles of nickel. The resulting mechanical stress changes may cause nickel to peel off from the electrolyte, thereby permanently changing the interface properties between nickel and the electrolyte. This change shortens the three-phase interface and reduces the charge transfer rate, ultimately affecting the anode reaction kinetics and electrochemical performance of direct ammonia proton ceramic fuel cells. Therefore, it is urgent to optimize the existing PCFC anode materials, and it is very important to enhance the mechanical strength of the anode and the conversion rate of ammonia. Summary of the invention

[0004] The technical problem to be solved by the present invention is that the Ni-based anode of the direct ammonia proton ceramic fuel cell easily reacts with ammonia to form compounds such as nickel nitride (Ni3N), which consumes the active sites on the nickel surface and increases the activation overpotential. More importantly, these unstable nitrides may partially decompose or transform at high temperatures, resulting in repeated nitridation and reduction cycles of nickel. The resulting mechanical stress changes may cause nickel to peel off from the electrolyte, thereby permanently changing the interface properties between nickel and the electrolyte, resulting in poor operating stability and low mechanical strength of the anode material.

[0005] In the process of preparing the anode material, the present invention uses a one-step method to directly add the Ni element into the anode to form the anode material, so as to obtain a better three-phase interface and higher mechanical strength, and use it as a direct ammonia proton ceramic fuel cell anode material to improve the catalytic activity of ammonia. 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ, achieving a breakthrough in performance and strength. This patent develops a high-strength composite anode material, Ni-BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ The preparation method and application thereof improve the catalytic activity and stability of the anode material to ammonia, and at the same time improve the mechanical strength of the material and reduce the impedance of the material, so that the battery prepared by the one-step anode has excellent electrochemical performance and good stability.

[0006] The first aspect of the present invention provides:

[0007] A composite anode material for a medium- and low-temperature solid oxide fuel cell, characterized in that the anode material has a general formula of Ni-ABO 3-δ , which is in BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ The oxide lattice of the material also uses some Ni substitution, where δ is the oxygen vacancy content. According to the metal oxide conversion, the NiO and BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ The mass ratio is (6-7):(3-4).

[0008] The second aspect of the present invention provides:

[0009] The method for preparing the above-mentioned anode material comprises the following steps:

[0010] The material is prepared by a sol-gel method. Ni salt, Ba salt, Zr salt, Ce salt, Y salt and Yb salt are dissolved in deionized water in sequence according to a stoichiometric ratio and heated and stirred evenly. A certain proportion of ethylenediaminetetraacetic acid, citric acid monohydrate and ammonia water are poured into the solution, the pH is adjusted to about 6-8, and heating and stirring are continued until the solution becomes a viscous gel state. After drying, the solution is calcined to obtain a powder.

[0011] The Ni salt, Ba salt, Zr salt, Ce salt, Y salt and Yb salt are nitrates of these metals.

[0012] Drying conditions: 150-200°C for 5-20h.

[0013] Calcination conditions: calcination at 900-1100℃ for 1-10h, heating rate 5-15℃min -1 .

[0014] The molar ratio of ethylenediaminetetraacetic acid: citric acid monohydrate: total metal ions is 1: (1.5-2.5): (0.5-1.5).

[0015] The third aspect of the present invention provides:

[0016] The anode material is used in the anode of a proton ceramic fuel cell or a direct ammonia fuel cell.

[0017] The anode adopts a composite anode material prepared by a one-step method, and starch is used as a pore-forming agent.

[0018] The mass ratio of the composite anode material to starch is 8-12:1.

[0019] A fourth aspect of the present invention provides:

[0020] An anode-supported proton ceramic fuel cell comprises the following steps:

[0021] The anode powder is first prepared into an anode support layer by dry pressing, and then a layer of electrolyte powder is spread on it, and then die-casting is performed to obtain a Ni-BCZYYb|BCZYYb half-cell. After calcination, the electrolyte of the half-cell is made dense, and then a layer of cathode material is sprayed on the surface of the electrolyte to obtain a Ni-BCZYYb|BCZYYb|PBSCF single cell, which is then calcined again to obtain a battery cell.

[0022] The calcination parameters of the half-cell were calcination at 1450 °C for 10 h;

[0023] The calcination temperature of the single cell is 1000°C for 2h.

[0024] Beneficial effect: The material involved in the present invention is Ni-BaZr prepared by one-step method. 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ (One-step anode) is used as the ceramic phase in the anode of proton ceramic fuel cells. The reduced Ni-BZCYYb anode has excellent catalytic activity for both ammonia decomposition reaction and hydrogen electrochemical oxidation. After testing, the single cell Ni-BCZYYb|BCZYYb|PBSCF prepared by the one-step anode has a maximum power density of 1050, 660, 430 and 300 mW cm in H2 atmosphere at 650, 600, 550 and 500 °C, respectively. -2 , the highest power densities in NH3 atmosphere reached 660, 465, 302 and 195 mW cm -2 . BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1: wherein a is the XRD spectrum of the one-step anode and the physical mixing anode of the present invention under air atmosphere, and b and c are the XRD refined spectrum of the one-step anode and the physical mixing anode, respectively.

[0026] Figure 2 : Wherein a is a SEM spectrum of a single cell prepared by a one-step anode according to the present invention. b is a schematic diagram of the morphology of a one-step anode according to the present invention, c is a SEM spectrum of a single cell prepared by a physical mixing anode according to the present invention, and d is a schematic diagram of the morphology of a physical mixing anode.

[0027] Figure 3 : Wherein a and b are the comparison diagrams of the ammonia catalytic activity of the one-step anode and the physical mixing anode after reduction at 500-700°C, and the schematic diagram of the catalyst stability of the one-step anode at 600°C and NH3 fuel.

[0028] Figure 4 : Wherein a, b, c and d are the IVP curves and impedance diagrams obtained by testing the single cell prepared with a one-step anode in H2 atmosphere and the single cell prepared with a physical mixing anode in the range of 500 to 650°C.

[0029] Figure 5 : Wherein a, b, c and d are the IVP curves and impedance diagrams obtained by testing the single cell prepared with a one-step anode in an NH3 atmosphere and the single cell prepared with a physical mixing anode in the range of 500 to 650°C.

[0030] Figure 6 : wherein a, b, c and d are the single cell prepared by the one-step anode method and the single cell prepared by the physical mixing anode method at 600 and 500°C at a current density of 200 mA cm -2 Thermal cycling stability and thermal cycling decay rate of a single cell operating on NH3 fuel.

[0031] Figure 7 : Deconvolution peak diagram of EIS of the one-step anode and the physical mixing anode involved in the present invention at 5 vol% H2O-H2 and 500°C after DRT fitting.

[0032] Figure 8 : It is the specific surface area analysis (BET) diagram of the one-step anode and the physical mixing anode involved in the present invention.

[0033] Fig. 9 : It is the mechanical strength analysis diagram of the one-step anode and the physical mixing anode involved in the present invention.

[0034] Fig.10: This is a temperature-programmed reduction (H2-TPR) diagram of hydrogen at the one-step anode and the physical mixing anode involved in the present invention. DETAILED DESCRIPTION

[0035] The present invention relates to a proton ceramic fuel cell battery structure and a preparation method thereof. In one embodiment, the battery cathode material has a molecular formula of PrBa 0.5 Sr 0.5 Co 1.5 Fe 0.5 O 5+δ (PBSCF), the electrolyte material composition formula is BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ (BZCYYb), the molecular formula of the anode material is Ni-BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ (Ni-BZCYYb), where δ represents the oxygen vacancy content. NiO and BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ The mass ratio of is 6.5:3.5, and the anode material is prepared by a one-step method.

[0036] Preparation of conventional anode material Ni-BaZr by one-step method 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ The electrochemical performance of proton ceramic fuel cells is improved by using the one-step anode method. Compared with the anode materials prepared by the traditional physical mixing method, the Ni and BZCYYb in the material have a strong interaction under a reducing atmosphere, which enhances the thermal stability and durability of direct ammonia fuel cells and significantly reduces the impedance. At 650°C, the maximum output power of the single cell Ni-BCZYYb|BCZYYb|PBSCF prepared by the one-step anode method is 1050 and 660 mW cm-3 when H2 and NH3 are used as fuels, respectively. -2 The maximum output powers of the single cell Ni-BCZYYb|BCZYYb|PBSCF prepared with physical hybrid anode are only 850 and 510 mW cm -2 , an increase of 23% and 29% respectively.

[0037] Embodiment 1:

[0038] This embodiment provides a method for preparing anode material Ni-BZCYYb prepared in one step, and the specific steps are as follows:

[0039] (1) Weigh 33.7867 g of barium nitrate, 5.5504 g of zirconium nitrate, 39.2959 g of cerium nitrate, 4.9516 g of yttrium nitrate, 5.8061 g of ytterbium nitrate and 252.9944 g of nickel nitrate, and dissolve them in a small amount of deionized water. Weigh 329.81 g of ethylenediaminetetraacetic acid and 474.3112 g of citric acid monohydrate as complexing agents in a molar ratio of ethylenediaminetetraacetic acid: monohydrate citric acid: total metal ions of 1:2:1 and dissolve them in deionized water.

[0040] (2) After adding the solution containing the complexing agent into the solution containing the metal ions, an appropriate amount of ammonia water is added dropwise until the pH of the solution reaches about 7, and then the solution is stirred under magnetic stirring until the water is completely evaporated to obtain a gel-like substance.

[0041] (3) Take out the rotor in the gel, seal the mouth of the beaker with aluminum foil to prevent it from overflowing, and then put the gel-like substance into a forced air drying oven and dry it at a constant temperature of 180°C for 5 hours to obtain the desired foam precursor.

[0042] (4) Take out the beaker, and after cooling, scrape the precursor into each crucible with a scraper, and place the precursor in a high-temperature muffle furnace and calcine it at 1000°C for 5 hours to obtain the desired powder.

[0043] Comparative Example

[0044] When preparing a traditional physical mixed anode material, the converted element ratio as in Example 1 is used, NiO, BZCYYb and soluble starch are mixed in a mass ratio of 65:35:10, added to a ball mill, ethanol is used as a solvent, the mixture is ball milled for 30 minutes, and then dried to obtain an anode powder.

[0045] Embodiment 2:

[0046] This embodiment provides a method for preparing a proton ceramic ammonia fuel cell anode powder Ni-BZCYYb, and the specific steps are as follows:

[0047] (1) Weigh 10 g of Ni-BZCYYb powder and 1 g of soluble starch, pour all into a ball mill, add appropriate amount of ethanol and ball mill for 30 min.

[0048] (2) Pour the milled anode powder solution into a mortar and blow a fan toward the mortar to accelerate the volatilization of anhydrous ethanol. At the same time, stir the solution continuously with a pestle until the ethanol is completely evaporated.

[0049] (3) Scrape the anode powder in the mortar with a scraper and put it into a 65°C constant temperature drying oven to dry for 5 hours to obtain the required Ni-BZCYYb anode powder.

[0050] Embodiment 3:

[0051] This embodiment provides a method for preparing a single cell (Ni-BCZYYb|BCZYYb|PBSCF) with PBSCF as a cathode, BZCYYb as an electrolyte, and Ni-BZCYYb as an anode support, and the specific steps are as follows:

[0052] (1) Weigh 0.35 g of the powder obtained in Example 2 and put it into a mold. Use a tablet press to press it into a tablet with a diameter of about 15 mm to obtain an anode green body.

[0053] (2) Weigh 0.015 g of BZCYYb powder and spread it evenly on the anode green body through a screen. Then put the mold into a tablet press to form an anode-electrolyte double-layer green body, which was sintered at 1450 °C for 5 h to obtain an anode-supported half-cell.

[0054] (3) Place the anode-supported half-cell on a heating table and set the temperature to 150°C. After the half-cell is evenly and fully heated, use a spray gun to evenly spray the PBSCF cathode slurry on one side of the electrolyte. Place the sprayed half-cell in a high-temperature electric furnace for heat treatment. The calcination temperature is 900-1100°C and the heating rate is 5°C min -1 The insulation time is 2h, and after cooling down, it is taken out to obtain the prepared single cell Ni-BCZYYb|BCZYYb|PBSCF.

[0055] Characterization results

[0056] 1. Phase structure and micromorphology

[0057] Figure 1 a is the XRD patterns of the one-step anode and the physical mixing anode at room temperature. The one-step anode only exhibits diffraction peaks corresponding to NiO and BZCYYb, which is consistent with the physical mixing anode powder. Figure 1Figures b and c are the XRD refinement patterns of the one-step anode and the physical mixing anode after reduction. The one-step anode is a composite electrode containing 45.77wt.% BZCYYb phase (pm-3m) and 54.23wt.% metal Ni phase (Fm-3m), while the mass ratios of BZCYYb and Ni after reduction by the physical mixing anode are 42.69wt.% and 57.31wt.%. Due to the residual Ni element in the main phase of BZCYYb in the one-step anode, the lattice parameter of the BZCYYb phase in the one-step anode (a=b=c=0.4377(6)nm) is greater than that in the physical mixing anode (a=b=c=0.4376(7)nm).

[0058] Figure 2 a is a SEM spectrum of a single cell prepared by a one-step anode according to the present invention. b is a schematic diagram of the morphology of a one-step anode according to the present invention, c is a SEM spectrum of a single cell prepared by a physical mixing anode according to the present invention, and d is a schematic diagram of the morphology of a physical mixing anode. It can be observed that the contact between the metal Ni and the BZCYYb phase in the one-step anode is closer and the phase distribution is more uniform.

[0059] 2. Analysis of anode ammonia catalytic activity

[0060] Figure 3 Figure a is a comparison of the catalytic activity of ammonia after reduction at 500-700°C between the one-step anode and the physical mixing anode. As can be seen from the figure, the catalytic activity of the one-step anode is indeed better than that of the physical mixing anode. For example, when the one-step anode is used as a catalyst, the NH3 conversion rate is about 70% at 500°C, while the NH3 conversion rate of the physical mixing anode catalyst is only about 60%. Figure 3 Figure b is a schematic diagram of the stability of the one-step anode after reduction at 600°C and NH3 fuel for ammonia catalytic activity. At 600°C, the one-step anode was kept in NH3 atmosphere for 200 hours, and the ammonia conversion rate did not significantly decay. It can be concluded that the one-step anode has better catalytic activity and higher stability.

[0061] 3. Single cell performance and impedance test (H2 atmosphere)

[0062] The prepared single cell was sealed on a quartz tube with silver glue and then placed in an experimental furnace. The cathode of the cell was exposed to the air atmosphere, and pure H2 was introduced into the anode side of the cell as fuel, and the flow rate of the fuel gas and the test temperature of the cell were controlled. The performance of the single cell prepared by the one-step anode and the single cell prepared by the physical mixing anode were compared at different temperatures. Figure 4 a and b are the IVP curves of a single cell prepared with a one-step anode under H2 atmosphere and the IVP curves of a single cell prepared with a physical mixing anode under H2 atmosphere. Figure 4 Figures c and d are impedance diagrams of a single cell prepared by a one-step anode and a single cell prepared by a physical mixing anode. As shown in the figure, at 650, 600, 550 and 500°C, the OCV values ​​are all greater than 1, indicating that the electrolyte is dense and the battery is well sealed.

[0063] The maximum output power of the single cell prepared by one-step anode is 1050, 660, 430 and 300 mW cm at 650, 600, 550 and 500 °C, respectively. -2 , the corresponding polarization impedances are 0.12, 0.18, 0.39 and 0.72Ωcm respectively 2 The maximum output power of the single cell prepared by physical mixing anode at 650, 600, 550 and 500℃ is 850, 625, 400 and 250mWcm respectively. 2 , the corresponding polarization impedances are 0.13, 0.25, 0.48 and 1.81Ωcm respectively 2 It is obvious that the one-step anode can greatly improve the output performance of a single cell using H2 as fuel when used as an anode ceramic phase, and the one-step anode provides better H2 decomposition activity as well as rapid ion diffusion and conductivity. At the same time, as the temperature increases, both the material transfer and charge transfer processes in the battery reaction are accelerated, indicating that the higher the temperature, the higher the catalytic activity of the electrode material, the more active the kinetic reaction, and thus the lower the polarization impedance.

[0064] 4. Single cell performance and impedance test (NH3 atmosphere)

[0065] The prepared single cell was sealed on a quartz tube with silver glue and then placed in an experimental furnace. The cathode of the cell was exposed to the air atmosphere, and pure NH3 was introduced into the anode side of the cell as fuel, and the flow rate of the fuel gas and the test temperature of the cell were controlled. The performance of the single cell prepared by the one-step anode and the single cell prepared by the physical mixing anode were compared at different temperatures. Figure 5 a and b are the IVP curves of a single cell prepared with a one-step anode in an NH3 atmosphere and the IVP curves of a single cell prepared with a physical mixing anode in an NH3 atmosphere. Figure 5 Figures c and d are impedance diagrams of a single cell prepared by a one-step anode and a single cell prepared by a physical mixing anode. As shown in the figure, at 650, 600, 550 and 500°C, the OCV values ​​are all greater than 1, indicating that the electrolyte is dense and the battery is well sealed.

[0066] The maximum output power of the single cell prepared by one-step anode is 660, 440, 300 and 190 mW cm at 650, 600, 550 and 500 °C, respectively. -2, the corresponding polarization impedances are 0.14, 0.26, 0.60 and 1.23Ωcm respectively 2 The maximum output power of the single cell prepared by physical mixing anode at 650, 600, 550 and 500℃ was 510, 330, 200 and 120mWcm respectively. -2 , the corresponding polarization impedances are 0.21, 0.42, 1.01 and 3.82Ωcm respectively 2 It is obvious that the one-step anode can significantly improve the output performance of single cells using NH3 as fuel in the anode ceramic phase.

[0067] 5. DRT Characterization

[0068] Figure 7 The deconvolution peaks of the EIS of the one-step anode and physical mixing anode samples at 5% water partial pressure and 500°C after DRT fitting are shown. According to the frequency range, it is divided into the high-frequency region (P1), the medium-frequency region (P2) and the low-frequency region (P3), which reflect charge transfer, ion transport or surface exchange, and surface oxygen diffusion, respectively. In general, the ion transport or surface exchange represented by the medium-frequency region is the main limiting step affecting the electrochemical reaction. By comparison, the impedance of the one-step anode battery in the high-frequency (>1000Hz), medium-frequency (10-1000Hz) and low-frequency (<10Hz) regions are reduced to varying degrees, indicating that compared with the physical mixing anode, the one-step anode has more obvious advantages in the interfacial charge transfer, ion exchange and surface mass transfer under ammonia fuel.

[0069] 6. Characterization of thermal cycling stability of single cells

[0070] Figure 6 Figures a and c are the voltage variation curves of the single cell prepared by the one-step anode and the single cell prepared by the physical mixing anode at 600℃ and NH3 as fuel. It can be seen from the figure that after 15 cycles, the voltage of the single cell prepared by the one-step anode dropped from 0.90 and 0.73V to 0.86 and 0.59V at 600℃ and 500℃, respectively, while under the same test conditions, the voltage of the single cell prepared by the physical mixing anode dropped from 0.54V to 0.18V at 500℃. At 600℃, after thermal cycling test, the performance of the single cell prepared by the one-step anode and the physical mixing anode was attenuated by 4.44% and 29.60%, respectively; however, the activity attenuation of the single cell prepared by the physical mixing anode at a lower temperature of 500℃ was as high as 67.53%, which was 47.65% higher than that of the single cell prepared by the one-step anode, which also proved that compared with the physical mixing anode, the one-step anode has better stability in the ammonia fuel environment.

[0071] 7. Catalyst specific surface area test

[0072] Figure 8 The specific surface area of ​​the anode of the one-step anode physical mixing method of the present invention is shown in the figure. It can be seen that the specific surface area of ​​the anode of the one-step anode reaches 6.59 m 2 g -1 , compared with 2.83m2 g of physical mixing anode -1 The improvement is 132%. This improvement may be attributed to the more uniform dispersion of Ni particles in the one-step anode.

[0073] 8. Characterization of catalyst mechanical strength

[0074] Fig. 9 The mechanical strength diagram of the one-step anode and the physical mixing anode of the present invention is shown. The fracture pressure of the one-step anode is 1.55×10 8 Pa, while the fracture pressure of the physical mixing method anode is 1.28×10 8 Compared with the physical mixing method anode, the one-step anode has higher mechanical strength, which effectively optimizes the problem of insufficient mechanical strength of current proton ceramic fuel cells.

[0075] 9. Catalyst H2-TPR Characterization

[0076] Fig.10 The present invention relates to a H2-TPR schematic diagram of a one-step anode and a physical mixing anode. The physical mixing anode exhibits three obvious H2 absorption peaks when the temperature rises. The α peak and the β peak represent the Ni 3+ To You 2+ The peak temperatures are 314 and 446 °C for the conversion of NiO and the subsequent reduction of Ni metal, respectively. The γ peak mainly comes from the reduction of bulk NiO. The initial absorption peak temperature of the one-step anode sample is 516 °C, which is significantly higher than that of the physical mixing anode, indicating that the interaction between the two phases is stronger.

Claims

1. A composite anode material for medium and low temperature solid oxide fuel cells, characterized in that: The general formula of anode material is Ni-ABO 3-δ , which is in BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ The oxide lattice of the material also uses some Ni substitution, where δ is the oxygen vacancy content. According to the metal oxide conversion, the NiO and BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ The mass ratio is (6-7):(3-4).

2. The method for preparing the composite anode material for medium and low temperature solid oxide fuel cells according to claim 1, characterized in that: The method comprises the following steps: preparing the material by a sol-gel method, dissolving Ni salt, Ba salt, Zr salt, Ce salt, Y salt and Yb salt in deionized water in sequence according to a stoichiometric ratio, heating and stirring the solution to obtain a uniform solution, pouring a certain proportion of ethylenediaminetetraacetic acid, citric acid monohydrate and ammonia water into the solution, adjusting the pH value to about 6-8, continuing to heat and stir the solution until the solution becomes a viscous gel state, and drying and calcining the solution to obtain a powder.

3. The preparation method according to claim 3, characterized in that: The Ni salt, Ba salt, Zr salt, Ce salt, Y salt and Yb salt are nitrates of these metals.

4. The preparation method according to claim 3, characterized in that: Drying conditions: 150-200°C for 5-20h.

5. The preparation method according to claim 3, characterized in that: Calcination conditions: calcination at 900-1100℃ for 1-10h, heating rate 5-15℃min -1 .

6. The preparation method according to claim 3, characterized in that: The molar ratio of ethylenediaminetetraacetic acid: citric acid monohydrate: total metal ions is 1: (1.5-2.5): (0.5-1.5).

7. Use of the anode material according to claim 1 in a proton ceramic fuel cell anode or a direct ammonia fuel cell.

8. The use according to claim 5, characterized in that The anode material is a composite anode prepared with starch as a pore-forming agent.

9. The use according to claim 8, characterized in that The mass ratio of anode material to starch is 8-12:1.

Citation Information

Cited By

  • Preparation method and application of R-P type perovskite anode catalyst based on A-site praseodymium element doping

    CN122224861A